Respuesta :
Answer:
m=7
Step-by-step explanation:
Replace all occurrences of + − with a single -. A plus sign followed by a minus sign has the same mathematical meaning as a single minus sign because 1⋅ − 1 = − 1
7(m-13)=-42
Divide each term by 7 and simplify.
m-13=-6
Move all terms not containing m to the right side of the equation.
m=7
Hope this helps!
Plz mark brainiest! =D
7(m+-13)=-42
(m+-13)=-42-7
(m+-13)=-49
m=-49+13
m=-36
i don't know if this correct or not
(m+-13)=-42-7
(m+-13)=-49
m=-49+13
m=-36
i don't know if this correct or not